Efektifitas Ekstrak Daun Sirih Merah (Piper crocatum) Terhadap Peningkatan Berat Badan Tikus Putih (Rattus novergicus) Jantan Kondisi Diabetes Yang Di Induksi Aloksan - Dharmayudha, Anak Agung Gde Oka; Anthara, Made Suma; Wiranata, I Made Agus; Sudimartini, Luh Made (Buletin Veteriner Udayana; Vol. 6 No. 2 Agustus 2014, 2014)
Purpose of this research is to learn the level of effectiveness of ethanol extract from red betel leaf (Piper crocatum) within increase weight of male white mouse in condition for diabetes mellitus. 20 male white mice (Rattus novergicus) in 3 mounth with weight between 190-250 gram which adapted during 2 weeks. It classified to be 5 groups random, each group consisty by 4 mice. The first treatment as a negative control (healty mouse) whitout giving treatment. The second treatment as alloxan positive control, the third treatment alloxan added by 2% suspension of ethaol extract from red betel leaf (dose 100 mg/kg bb) per oral. The fifth treatment is alloxan added by 0.02% suspension glibenclamide (dose 1 ml/kg bb) per oral. Giving extract betel leaf is done by oral with used sonde. Giving treatment at treatment III, IV and V is done everyday start from day 3 until the end of the day (21 day). The weight of mouse is measure at day 7, 14 and day 21 used analytical balanced. The result of this research show up that giving 2% ethanol extract from red betel leaf (Piper crocatum) with dose (50 mg/kg bb), dose (100 mg/kg bb) and glibenclamide 0,02% ( 1 ml/kg bb) with significant can increase weight (P<0,05) of white mice which induce alloxan. Result of this research could be conclude that ethanol extract of red betel leaf (Piper crocatum) can used for increase the weight.